Oligodendrocytes and myelination: pioneering new frontiers in cognitive neuroscience - Zhang, Ning; Yi, Rulan; Zhong, Fuwang; Lu, Yali; Chen, Wenjia; Ke, Zhidan; Zhang, Yi; Zhou, Liang; Wang, Pengyu; Li, Wei (Frontiers in Neuroscience, 2025)
There has been a growing interest in the role of oligodendrocytes (OLs) and the myelin sheaths they form around axons in cognitive function. Historically, OLs were primarily considered to be involved in axonal insulation and signal transmission within the central nervous system (CNS). However, an increasing body of research indicates that OLs and myelination are integral to neural circuit formation, the regulation of plasticity, and higher-order cognitive functions. Developmental and functional abnormalities in OLs, as well as deficits in myelination, are pathologically associated with diseases characterized by clinical cognitive dysfunction. These abnormalities have significant implications for the development of diagnostic and therapeutic strategies for neurological disorders and for the advancement and innovation of treatment methodologies. Investigations into the impact of OLs and myelination on cognitive function offer a novel perspective for understanding the development, plasticity, and pathophysiological mechanisms of the nervous system. Future research endeavors are anticipated to elucidate the complexities of OLs and myelination, thereby offering renewed prospects for the diagnosis and treatment of neurological disorders. This review provides a systematic examination of contemporary research concerning OLs and myelination, covering fundamental mechanisms, their roles in cognitive function, recent clinical advancements, emerging therapeutic strategies, ongoing scientific debates, key challenges, and future directions. By incorporating multidisciplinary perspectives, this synthesis seeks to establish a comprehensive framework that will guide subsequent investigations in this domain.